GEORGIA’S ETHNIC HISTORY AND THE PRESENT MIGRATION PROCESSES - KOMAKHIA, Mamuka (CENTRAL ASIA AND THE CAUCASUS, 2008)
Georgia’s ethnic composition, which changed from one historical epoch to another, is a product of certain political, social, and economic factors. This led to certain migration trends that changed the size of particular ethnic groups. Georgian academic Vakhtang Jaoshvili identified the major stages in the process that led to changes in Georgia’s ethnic composition: From the Middle Ages to the late 18th century. from the early 19th century to the establishment of Soviet power in 1921, and from 1921 to the Soviet Union’s disintegration.1 Today we can speak about the fourth stage: from 1991, when Georgia became independent, to the present day. Throughout the Middle Ages Georgia remained the victim of its aggressive neighbors, whose regular inroads led to many deaths among the local residents and to their mass migration to the country’s central areas. The vacated lands were seized by ethnically alien peoples. Muslims moved into Kvemo Kartli in the latter half of the 15th century; during feudalism Ossets left the Northern Caucasus to settle in Eastern Georgia; and Greeks came to some of the Eastern Georgian villages in the latter half of the 18th century. The number of migrating aliens to feudal (normally self-contained) states was negligible, which explains the numerical domination of the Georgians in nearly every province.By the early 19th century, Georgians comprised four-fifths of the local population.2